THE STUDENT´S LEAGUE OF FRIENDS: STUDENT´S SOCIAL SKILLS DEVELOPMENT FOR PROVIDING SOCIAL AND EMOCIONAL SUPPORT - Benítez Muñoz, Juan Luís; Tomás De Almeida, Ana María; Justicia Justicia, Fernando (Anales de Psicología / Annals of Psychology, 2007)
Integrated in the European project TMR - Training and Mobility for researchers about nature and prevention of bullying against school violence and the Comenius Socrates Project, is developed the programme Education for Coexistence in Educative Contexts which main goal is to prevent bullying. One intervention way established in this programme has students as target population. In this article we present the training programme called Stu-dents League of Friends as well as the main evaluation results. It is a social and emotional support programme among students which main objective is to endow the students the communicative and helping skills which are necessary to establish positive relationships, as well as supporting relation-ships with other companions at risk. For such purpose, we specifically work students’ social skills. The collected data point out an improvement in the students who participated in the training programme that is related with a significant improvement of their social skills in comparison with students who did not receive any formation. The data allows us to show a development in social skills such as empathy, assertiveness, problem reso-lution skills, etc.